2014
DOI: 10.4238/2014.april.16.9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in the leptin gene associated with growth and carcass traits in Nellore cattle

Abstract: ABSTRACT. The aim of the study was to detect polymorphisms in the leptin gene and to determine the association of these polymorphisms with growth and carcass traits in Nellore cattle. The single nucleotide polymorphisms (SNPs) -1457 (AJ571671:g.-1457A>G) and A59V (AF536174.1:g. 321C>T), as well as the microsatellite BM1500 (3.9 kb downstream), were genotyped. The measures of body weight and ultrasound examinations (rib eye area, back, and rump fat thickness) were performed in 3 different periods of animal mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
2
19
2
1
Order By: Relevance
“…The polymorphism A80V of the LEP gene has been reported as an effective marker on weight and average daily body weight gains (Kulig and Kmieć, 2009), marbling and carcass traits in feedlot cattle (Geary et al, 2003;Silva et al, 2014). However, there was no association between the LEP A80V polymorphism and any of the phenotypic traits evaluated in the current study.…”
Section: Discussioncontrasting
confidence: 53%
“…The polymorphism A80V of the LEP gene has been reported as an effective marker on weight and average daily body weight gains (Kulig and Kmieć, 2009), marbling and carcass traits in feedlot cattle (Geary et al, 2003;Silva et al, 2014). However, there was no association between the LEP A80V polymorphism and any of the phenotypic traits evaluated in the current study.…”
Section: Discussioncontrasting
confidence: 53%
“…Subsequently, significant associations were revealed between the exon 2 polymorphisms of the LEP gene and the carcass fat distribution, the intensity of red muscle coloration, pH, marbling, and post-slaughter fat thickness traits in Nellore cattle (de Oliveira et al, 2013). Likewise, the other two LEP SNPs (g.− 1457A N C and g.321C N T) were identified in Nellore cattle, and the sense mutation (g.321C N T) was associated with rump fat thickness and muscle color post-slaughter (Silva et al, 2014). It has also been shown that the LEP gene associates with carcass yield and meat quality in beef cattle Tian et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…WANG et al, (2015) have found six novel mutations in LEP gene, which have been associated with growth traits in six native Chinese goat breeds. On the other hand, some SNPs have been found to be associated growth traits in cattle (YANG et al, 2007;SILVA et al, 2014). In terms of SNPs examined in LEP gene, Honamli and Hair goat breeds were found monomorphic.…”
Section: Yijklmno = μ + Ai + Bj + Ck + DL + Fm + Gn + Eijklmnomentioning
confidence: 97%
“…The growth is affected by many factors such as genetics, litter size, sex and environment in small ruminants. There are many of studies on different potential candidate genes related with growth-associated traits in varied livestock breeds, among these genes are GH, POU1F1, LEP, MSTN and BMP15 (SILVA et al, 2014;AN et al, 2011;SELVAGGI et al, 2011;LI et al, 2008).…”
Section: Introductionmentioning
confidence: 99%